2022
DOI: 10.3389/fped.2022.908963
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced serum immunoglobulins in clinical subtypes of pediatric tuberculosis disease

Abstract: Immune response to tuberculosis (TB) has been extensively studied in the past decades and classically involves cellular immunity. However, evidence suggests that humoral immunity may play a relevant role. Past studies regarding serum immunoglobulin (Ig) levels in TB are dated and only involve adult subjects. In this study, we retrospectively studied a cohort of 256 children with TB disease and analyzed 111 patients screened for total serum Ig at diagnosis. According to the severity and extent of organ involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Hassanein et al identified a case of miliar tuberculosis in a 31-year-old man [53]. Of note, as reported by Consonni et al, SIgMD may be associated with a severe clinical course of Mycobacterium infection compared to other healthy children [54]. Other infectious manifestations, such as skin infections [20,21,[55][56][57], multiple recurrent hordeola [58], chronic gastritis, cholecystitis, and epididymitis [15], have been reported in these patients.…”
Section: Clinical Manifestations (Table 4)mentioning
confidence: 86%
See 1 more Smart Citation
“…Hassanein et al identified a case of miliar tuberculosis in a 31-year-old man [53]. Of note, as reported by Consonni et al, SIgMD may be associated with a severe clinical course of Mycobacterium infection compared to other healthy children [54]. Other infectious manifestations, such as skin infections [20,21,[55][56][57], multiple recurrent hordeola [58], chronic gastritis, cholecystitis, and epididymitis [15], have been reported in these patients.…”
Section: Clinical Manifestations (Table 4)mentioning
confidence: 86%
“…Severe infections (meningitis, osteomyelitis, septic arthritis, and deep tissue and liver abscesses) and sepsis (mainly meningococcal and pneumococcal infections; Pseudomonas). Mycobacteria infections (also miliar tuberculosis [53] and atypical mycobacterial adenitis [54]). Soft tissue infections and skin infections (also herpes infections, acne conglobate [25], disseminated molluscum contagiosum in a 16-year-old girl [55], recurrent Staphylococcal pyoderma in two adult men [56], and recurrent impetigo in a 6.5-year-old boy [57].…”
Section: Upper Respiratory Tract Infectionsmentioning
confidence: 99%
“…The immune response to Mtb infection in different parts of the organism is diverse and complex (Consonni et al, 2022 ). As a consequence, safe and effective treatment requires precise control of the immune system.…”
Section: Discussionmentioning
confidence: 99%